Phenotypic and molecular diversity and genotype stability analysis of torch ginger [Etlingera elatior (Jack) R.M. Sm.] germplasm in peninsular Malaysia - Ismail, Nor Asiah (2018)
Torch ginger, Etlingera elatior is a potential source of natural antioxidant and antibacterial in food and pharmaceutical industries. It has been identified to have high market potential among 30 popular herbs or industrial new crops in Malaysia. Hitherto, limited information is available on their genetic resources and studies on its cultivation despite its importance in the diet of Southeast Asian population. Therefore, there is a need to conduct studies on the evaluation of the genetic diversity for breeding and conservation purposes. Furthermore, the evaluation of potential genotypes under different environments is an important step in breeding programs to select the promising accessions for future torch ginger development. Fifty seven accessions of torch ginger were collected from seven states in Peninsular Malaysia and evaluated for their agromorphological and molecular (Inter Simple Sequence Repeat (ISSR) and Microsatellite, Simple Sequence Repeat (SSR) markers) characterization to assess the pattern of genetic diversity and association among the characteristics. The screening of phytochemical characteristics such as antioxidant activity and total phenolic content were conducted on all the accessions. Diversity study through agro-morphological and molecular markers showed that high variability existed among the 57 torch ginger accessions. Morphological traits and molecular markers by ISSR and SSR revealed the presence of high genetic variability among the torch ginger accessions. This study found that SSR marker was more informative compared to ISSR marker in the determination of gene diversity, polymorphic information content (PIC) and heterozygosity in this population. High level of genetic diversity discovered by SSR markers showed the effectiveness of this marker to detect the polymorphism in this germplasm collection. In terms of antioxidant activity, different accessions were observed to have varying degrees of free radical scavenging activities (1397.08 to 4356.84 mg AA/100 g) and total phenolic content (874.53 to 2763.62 mg GAE/g). Out of the 57 accessions, 15 were selected based on high flower yield (>40 flower buds per year) or high antioxidant activity (>3000 mg AA/100 g) or both traits for genotype by environmental interaction (GxE) evaluation at three different locations, namely Jerangau, Terengganu; Jelebu, Negeri Sembilan and Jalan Kebun, Selangor. However, the trial plot at Jalan Kebun was destroyed by flooding after one year of planting. The 15 selected accessions were evaluated at two locations (Jerangau and Jelebu) for morpho-physiological traits, yield components, antioxidant activity and total phenolic content. Highly significant differences were observed from the analysis of variance over the two locations among the accessions (G), locations (L), and accessions by locations interaction (GxL) for all the traits except plant height, bud length and bud dry weight. This result indicated that G, L and GxL interaction affected yield traits and phytochemical activity such as antioxidant activity and total phenolic content in this torch ginger population. From multivariate stability analysis three accessions, KAN035, KAN061 and KAN023 were the most ideal genotypes for high yield character and high genotype stability across environments. These accessions are recommended for future torch ginger breeding program for varietal development with high flower yield and high antioxidant characteristics.